Intravenous Lidocaine for Opioid-Resistant Pain Control in Metastatic Breast Cancer (Archives of Clinical and Medical Case Reports, 2021)
A fifty-one-year-old woman presented with pain related to metastatic breast cancer. The palliative care team was consulted for acute pain management intervention. At home, she was taking methadone for pain control. However, shooting pains down her legs had progressed to an unmanageable level, to the point where she was confided to bed. She was admitted to the hospital and was started on a hydromorphone PCA without complete pain control. Intravenous lidocaine was trialed and significantly improved the patient’s pain and decreased the need for other opioid medications. After these results, she was started on a lidocaine drip without side effects noted.